Impaired Adipose Tissue Expandability and Lipogenic Capacities as Ones of the Main Causes of Metabolic Disorders - Isabel Moreno-Indias; Francisco José Tinahones (Journal of Diabetes Research)
Obesity is considered a major health problem. However, mechanisms involved and its comorbidities are not elucidated. Recent theories concerning the causes of obesity have focused on a limit to the functional capacity of adipose tissue, comparing it with other vital organs. This assumption has been the central point of interest in our laboratory. We proposed that the failure of adipose tissue is initiated by the difficulty of this tissue to increase its cellularity due to excess in fat contribution, owing to genetic or environmental factors. Nevertheless, why the adipose tissue reduces its capacity to make new adipocytes via mesenchymal cells of the stroma has not yet been elucidated. Thus, we suggest that this tissue ceases fulfilling its main function, the storage of excess fat, thereby affecting some of the key factors involved in lipogenesis, some of which are reviewed in this paper (PPARγ, ROR1, FASN, SCD1, Rab18, BrCa1, ZAG, and FABP4). On the other hand, mechanisms involved in adipose tissue expandability are also impaired, predominating hypertrophy via an increase in apoptosis and a decrease in adipogenesis and angiogenesis. However, adipose tissue failure is only part of this great orchestra, only a chapter of this nightmare.